Corruption and inflation in agricultural production: The problem of the chicken and the egg - Paulo Peixoto de Albuquerque; Vítor Jo\~ao Pereira Domingues Martinho; Paulo Mour\~ao (Economies, 2022)
Corruption and inflation are two economic problems with serious social consequences. This paper analyzes the link between these two problems, focusing on the case of 19 prices observed for agricultural products in 90 countries since 2000. Using 'panel data cointegration' techniques, we conclude that, in most cases, there is a long-term relationship between inflation and corruption. The direction of causality favors the hypothesis that the inflation of agricultural products promotes incentives that lead to an increase in corruption levels. These results have important implications in terms of fighting corruption, giving special attention to controlling inefficiencies in agricultural markets that lead to higher prices that are then tapped into corruption mechanisms.
Keywords: 330; corruption; inflation; panel cointegration; production price levels